(untitled) (Fiep Bulletin - online, 2014)
Abstract: Qualitative research about the adventure of dancing on wheel chairs. Semi-structured interviews, Analysis of Speeches, Free idea associations and projective proof of animals’ Allegories were done with wheel chair sitters, intending to find an animal which would represent this dance. Our challenge was to identify through these animals’ allegories, projective dreams, and full of images. Ideas of ascension, heroism, strength, potency, flow, expansion, liberty, Love, over substantiate this dance of human manifestation, choreographed in the soul’s completeness. To reach it, we need to keep away from the party and, between the contemplation and the praxis, meet the scenario, identify the twenty actors and their speeches, discovering and improving new flights and cultural manifestations, modifying the social meaning of the wheelchairs, reaching over barriers when there is desire and pleasure on speaking louder. We need to re-think this dance, understanding how the body interprets, wins and arouse senses in people, in a socio-historic-cultural relation, going beyond the speeches about body thought in the dance and body thought of the dance. Dancing to these actors is an adventure, life on the movement. Body makes the wheelchairs an instrument, a transport to movement, a choreographically art. Through practice, these bodies, partially mobilized, let their feelings, emotions and spirit talk. They live temporarily, by the utopia, their double, the metaphoric moment, rupture, their dances, their animals’ allegories, which give these bodies the sense of being alive, at the aesthetic substratum of re-meaning of looks. This way, they let emerge their birds, eagles, condors, peacocks, lions, panthers, leopards, horses, dogs, cats. They reinvent each movement, plotting them with new hues, reaching thought dimensions and nature humanized, where wheels, movement, adventure of dancing make them forget the racism, social values, exclusion, dancing identity and prepare to the next flight…